Enhancing Students’ Levels of Understanding of the Sun–Earth System through a Phenomena-Driven Instruction Model Supported by Bi-Model Media - Kadek Dewi Wahyuni Andari; Andi Suhandi; Ida Kaniawati; Cepi Riyana; Mohd Zaidi Bin Amiruddin (Universitas Muhammadiyah Makassar, 2026)
Understanding Sun–Earth system phenomena remains challenging for many students because the underlying astronomical mechanisms involve cosmic-scale objects, spatial relationships, and dynamic processes that cannot be directly observed in their entirety. These difficulties often lead to an incomplete understanding and persistent misconceptions about insolation, variations in day and night lengths, and seasonal changes. This study aimed to investigate changes in preservice elementary teachers’ conceptual understanding of the Sun–Earth system after the implementation of the Phenomena-Driven Instruction (PhDI) model, assisted by Bi-Model media. A pre-experimental method with a one-group pretest–posttest design was employed. The participants were 36 second-year students enrolled in an Elementary Teacher Education Program at a university in North Kalimantan, Indonesia. The instructional intervention was implemented through five stages of the PhDI model supported by Bi-Model media consisting of physical and virtual representations of the Sun–Earth system. Data were collected using the Level of Conceptual Understanding Test (LCUT), which covered four concepts: insolation, day and night duration, winter, and summer. The instrument was validated by five experts and demonstrated good internal consistency, with a Cronbach’s alpha coefficient of 0.80. The results showed a consistent shift from lower levels of understanding, including partial understanding with misunderstanding, misunderstanding, and no understanding, toward higher levels, particularly partial understanding and sound understanding. The percentages of students reaching sound understanding were 52% for isolation, 58% for day and night duration, and 61% for both winter and summer. The novelty of this study lies in integrating phenomena-driven learning with dual physical and virtual model representations to support conceptual reconstruction of astronomical concepts. These findings suggest that PhDI assisted by Bi-Model media can support more scientifically acceptable explanations of Sun–Earth system phenomena and contribute to physics education by offering an instructional approach for teaching abstract, cosmic-scale concepts to preservice elementary teachers.